FEEDING PROCESSED Vitamin A CASSAVA ROOT MEALS TO BROILER CHICKENS: PERFORMANCE CHARACTERISTICS, BLOOD INDICES AND ANTIOXIDATIVE STATUS - obakanurhe, oghenebrorhie (Archives of Veterinary Science, 2024)
The emerging effects of climate change and the increasing cost of grains have been a serious issue to animal nutritionist in the tropics. This study evaluates the performance of broiler finisher chickens fed different processed cassava UMUCASS 36 (vitamin A) root meals (PCRM) as substitute for maize in the diets of 108 Arbor Acre (starter) finisher chickens for 21days. Six diets were formulated and the test diet was supplemented to the birds as partial and whole. The birds were fed T1 as the control, T2 had 25% each of oven-dried and sun-dried cassava root meal, T3 had 25% maize and 25% oven-dried cassava root meal, T4 had 25% maize and 25% sun-dried cassava root meal, while T5 had only 50% oven-dried cassava root meal, and T6 also had only 50% sun-dried cassava root meal respectively. Data were collected on the performance characteristics, blood indices and serum antioxidant of the birds. Performance characteristics of the birds revealed that T4 recorded significant (p<0.05) values of 2722.32 g, 1559.62 g and 1.61 final weight, weight gain and FCR respectively in comparison to the other treatments. The test diets did not show any adverse effect on the haematology and serum biochemistry of the birds. However, on the serum antioxidant status, T5 and T6 showed better values on the Aspartate aminotransferase and Alanine aminotransferase of the birds. The result on Superoxide dismutase and Malondialdehyde of the birds revealed that T4 and T6 recorded higher and lower values respectively. It was concluded that broiler finisher chickens could be fed up to 50% processed cassava root meal, inclusion using both techniques without detrimental effects.